Ecological Emergy Accounting for a Limited System: General Principles and a Case Study of Macao - Lei, Kampeng; Zhou, Shaoqi; Wang, Zhishi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book builds on the analyses of Eugene and Howard Odum and introduces the concept of systems ecology. Ecological emergy accounting represents a breakthrough because it allows researchers to integrate man-made capital and natural capital so that human and natural concerns can be addressed using a consistent system of units. This book develops an emergy accounting model that is suitable for describing urban systems, thereby providing a comprehensive picture of those systems. To make the theory concrete, the authors use China$1 (Bs Macao Special Administrative Region as a case study, and compare the results for Macao with those of other urban ecosystems around the world in the fields of ecological economy, tourism, waste treatment, gambling industry, land reclamation and resource consumption etc. Dr. Kampeng Lei is a scientist of Macau Science and Technology Association, Macao, China; Shaoqi Zhou is a professor at the College of Environment and Energy, the South China University of Technology, and the Guizhou Academy of Sciences, China; Zhishi Wang is a professor at the Faculty of Science and Technology, the University of Macau, Macao, China.s
From the Contents: Emergy Synthesis and Ecological Energy Accounting -- Emergy Synthesis for Eco-economic Systems of Macao -- Emergy analysis for tourism systems: principles and a case study for Macao -- Ecological energy accounting for the gambling sector: a case study in Macao -- Emergy Synthesis of Waste Treatment in Macao -- Per capita Resource Consumption and Resource Carrying Capacity: a Comparison of the Sustainability of 17 Mainstream Countries.
Keywords: Environmental sciences; Engineering economy; Environmental management; Environment; Environmental Management; Energy Policy, Economics and Management; Energy Economics; Energy Policy, Economics and Management